Childhood Neurogenic Stuttering Due to Bilateral Congenital Abnormality in Globus Pallidus: A Case Report and Review of the Literature - SAEEDI BORUJENI, Mohammad Javad; ESFANDIARY, Ebrahim; ALMASI DOOGHAEE, Mostafa (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Saeedi Borujeni MJ, Esfandiary E, Almasi Dooghaee M. Childhood Neurogenic Stuttering Due to Bilateral Congenital Abnormality in Globus Pallidus: A Case Report and Review of the Literature. Iran J Child Neurol. Autumn 2016; 10(4):75-79. Abstract Objective The basal ganglia are a group of structures that act as a cohesive functional unit. They are situated at the base of the forebrain and are strongly connected with the cerebral cortex and thalamus. Some speech disorders such as stuttering can resulted from disturbances in the circuits between the basal ganglia and the language motor area of the cerebral cortex. Stuttering consists of blocks, repetitive, prolongation or cessation of speech. We present a 7.5 -year-old male child with bilateral basal ganglia lesion in globus pallidus with unclear reason. The most obvious speech disorders in patient was stuttering, but also problems in swallowing, monotone voice, vocal tremor, hypersensitivity of gag reflex and laryngeal dystonia were seen. He has failed to respond to drug treatment, so he went on rehabilitation therapy when his problem progressed. In this survey, we investigate the possible causes of this type of childhood neurogenic stuttering. References 1. Daliri A, Prokopenko RA, Flanagan JR, Max L. Control and Prediction Components of Movement Planning in Stuttering Versus Nonstuttering Adults. J Speech Lang Hear Res 2014;57(6):2131-41. 2. Kasbi F, Mokhlesin M, Maddah M, Noruzi R, Monshizadeh L, Khani MMM. Effects of Stuttering on Quality of Life in Adults Who Stutter. Middle East J Rehab Health 2015;2(1). e43352, DOI: 10.17795/ mejrh-25314 3. Alm PA. Stuttering and the basal ganglia circuits: a critical review of possible relations. J Communicat Disord 2004;37(4):325-69. 4. Groenewegen HJ. The basal ganglia and motor control. Neural Plasticity 2003;10(1-2):107-20. 5. Van Schouwenburg MR, Onnink AMH, Ter Huurne N, Kan CC, Zwiers MP, Hoogman M, et al. Cognitive flexibility depends on white matter microstructure of the basal ganglia. Neuropsychologia 2014;53:171-7. 6. Albin RL, Young AB, Penney JB. The functional anatomy of basal ganglia disorders. Trends Neurosci 1989;12(10):366-75. 7. Tani T, Sakai Y. Analysis of five cases with neurogenic stuttering following brain injury in the basal ganglia. J Fluency Disord 2011;36(1):1-16. 8. Ludlow CL, Loucks T. Stuttering: a dynamic motor control disorder. J Fluency Disord 2004;28(4):273-95. 9. Van Borsel J, Van Der Made S, Santens P. Thalamic stuttering: A distinct clinical entity? Brain Language 2003;85(2):185-9. 10. Nambu A. Functional Circuitry of the Basal Ganglia. Deep Brain Stimulation for Neurological Disorders: Springer; 2015. p. 1-11. 11. Jin X, Tecuapetla F, Costa RM. Basal ganglia subcircuits distinctively encode the parsing and concatenation of action sequences. Nature Neurosci 2014;17(3):423-30. 12. Volkmann J, Hefter H, Lange H, Freund H-J. Impairment of temporal organization of speech in basal ganglia diseases. Brain Lang 1992;43(3):386-99. 13. Civier O, Bullock D, Max L, Guenther FH. Computational modeling of stuttering caused by impairments in a basal ganglia thalamo-cortical circuit involved in syllable selection and initiation. Brain Lang 2013;126(3):263-78. 14. Giraud A-L, Neumann K, Bachoud-Levi A-C, von Gudenberg AW, Euler HA, Lanfermann H, et al. Severity of dysfluency correlates with basal ganglia activity in persistent developmental stuttering. Brain Lang 2008;104(2):190-9. 15. Mink JW. The basal ganglia and involuntary movements: impaired inhibition of competing motor patterns. Arch Neurol 2003;60(10):1365-8. 16. Watkins KE, Smith SM, Davis S, Howell P. Structural and functional abnormalities of the motor system in developmental stuttering. Brain 2008;131(1):50-9. 17. Allert N, Kelm D, Blahak C, Capelle H-H, Krauss JK. Stuttering induced by thalamic deep brain stimulation for dystonia. J Neural Transm (Vienna) 2010;117(5):617-20. 18. Dietz J, Noecker AM, McIntyre CC, Mikos A, Bowers D, Foote KD, et al. Stimulation region within the globus pallidus does not affect verbal fluency performance. Brain Stimulation 2013;6(3):248-53. 19. Ullman MT. Is Broca’s area part of a basal ganglia thalamocortical circuit? Cortex 2006;42(4):480-5.